Tutor role in combating evasion in the EAD: professional perceptions of a higher education institution - Bizarria, Fabiana Pinto de Almeida (2015)
The study aims to analyze the role of mentoring in fighting evasion in distance education in perceptions of professionals of a higher educational institution of Ceará. For the field study, the methodological approach used was the case study, supported in data obtained through eight semi-structured interviews, research and consultations in organizational documents. The interpretation of the data was carried out based on the elaboration of the following categories: Attendance Tutor, Tutor Profile; Turnover Tutor; Importance of the Tutor; Strategies; Professor versus Tutor; Assiduity of Tutors; Building Links. The tutor emerges as the most professional impact on students’ permanence assurance, by virtue of their position in the distance education system, which ensures greater direct contact with the student.